(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
To evaluate potential fire danger based on weather conditions the region of South Siberia’s Mountains (80–110º E and 50–58º N) we used a correlation relationship between a number of days with high fire danger (Nesterov Index > 1000) and the hydrothermal coefficient (HTC) of Selyaninov (Malevsky-Malevich et al., 2005), which is a ratio of monthly temperature to precipitation. Based on predicted HTC at 2040–2060 derived from the climate model INM-CM5-0 and moderate (ssp 126) and extreme (ssp 585) scenarios of CMIP6, "hot spots" of dryer climates and increased numbers of days with high fire danger were mapped across the study region with a focus on mountain forests.